Peran Orang Tua dan Sekolah dalam Maksimalisasi Pembelajar Mandiri di Masa Pandemi Covid-19 - I Made Suardana (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
This research was raised because in pandemic times, students have to learn from home, and this requires independence. To bring out details about the role of parents and schools, researchers conducted literature research by studying in-depth independent learners. From the analysis results of various relevant library sources, the authors found that parents and schools need to establish cooperation to establish a mentoring section for students. Then parents and schools need to work together in building positive habits. However, there are obstacles that can arise, namely the busyness of parents who work, and parental understanding is still limited. Some parental support in the maximization of independent learners in pandemic times is to provide encouragement that will spur the development of self-potential, emotional support because the pandemic period can cause difficulties for students, motivation to keep learning passions high, and physiological support by ensuring students' health is especially not exposed to Covid-19.